PERSEPSI SISWA SMA DI KOTA CIREBON TERHADAP EFEKTIVITAS MEDIA DIGITAL DALAM PEMBELAJARAN EKONOMI PADA MATERI PERMINTAAN DAN PENAWARAN - Uswatun Hasanah (FKIP Unswagati, 2025)
The purpose of this study is to explore the views of high school students in Cirebon regarding how effective digital media is in the learning process of economics, focusing on the topic of demand and supply. This study applied qualitative methods and collected data through questionnaires. The participants in this study were high school students who were selected by purposive sampling. Findings from the study showed that many students felt the positive impact of using digital media in economics lessons. The media helps students understand complex economic concepts by showing interactive graphics and simulations. In addition, the use of digital media is also able to increase students' interest in the subject matter because of the interesting and not boring way of delivery. However, there are some challenges that arise, such as problems with internet connection, device limitations, and lack of support from teachers. These challenges emphasize the importance of developing technological infrastructure and training for teachers to support digital learning. Students' expectations for the use of digital media include the desire for more frequent use, the incorporation of digital media with traditional teaching methods, and the improvement of teachers' ability to use technology effectively. The conclusion of this study is that digital media has great potential to improve the effectiveness of economic learning. However, to maximize these benefits, there needs to be comprehensive support in terms of infrastructure, training for teachers, and sufficient technical guidance. Keywords: Students' views, digital media, economic learning, supply and demand, learning success